The Health Effects of Modern Gaming Devices and Phones n the Child's Mind and Intellectual Level - Jawad, Aseel Hafedh; Al-Kazazz, Zainab Kareem; AlKhafaji, Naiel A.K. (South Eastern European Journal of Public Health, 2024)
This study included 200 children between the ages of 2-12 years, who use mobile phones for multiple purposes. This study was conducted by distributing questionnaires to parents, and their answers were approved for their children. This study showed that the age group >=5 years had the highest percentage, reaching 60% of children. The study sample was mostly females (girls) at 54%, while the remaining section was males (boys) at 46%. This study showed that children in an urban environment use mobile phones more than children who live in a rural environment, where their percentage reached (66%). The study showed that the educational level of the parents of these children was good, as most of them held a university degree (38.0%, 36. %) for both the mother and the father, respectively. The study showed a significant relationship P = 0.0001 between parents’ occupation and Children used mobile phones and gaming devices, and the percentage was higher if both parents worked (42% and 78%) for the mother and father, respectively. The study showed that most children belong to a middle-income family environment. The study showed that the percentage of children who use modern phones and gaming devices reached (96%), while those who do not use mobile phones (4%). Most of the families had more than two phones at home (58%), and (78%) of the children used the phone throughout the day, and (48%) of them felt happy as a result of using the mobile phone, and (52%) of the study sample used the mobile phone for a period of time. (two years or more). The study showed that 56% of children suffer from lack of concentration and a low level of intelligence. According to the results of the study, 54% of them suffer from problems in their fingers as a result of frequent use of toys, and 70% of children suffer from dry eyes and a constant feeling of sleepiness as a result of radiation emitted from toys and devices. 93% of them suffer from anxiety and depression. The study also showed that (72%) of the children were addicted to the phone and the phone caused them headaches. It is clear from this study that children’s use of the phone causes them many problems, including psychological and physical ones. Therefore, parents must keep their children away from mobile phones as much as possible, and if they have to, allow them to use them. There must be a specific time for using phones, and the harmful effects of phones must be explained to them, whether in the short or long term.